Advances in Automated Valuation Modeling AVM After the Non-Agency Mortgage Crisis - d'Amato, Maurizio; Kauko, Tom.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book addresses several problems related to automated valuation methodologies (AVM). Following the non-agency mortgage crisis, it offers a variety of approaches to improve the efficiency and quality of an automated valuation methodology (AVM) dealing with emerging problems and different contexts. Spatial issue, evolution of AVM standards, multilevel models, fuzzy and rough set applications and quantitative methods to define comparables are just some of the topics discussed.
A Brief Outline of AVM Models and Standards Evolutions -- Appraisal methods and the non-agency mortgage crisis -- Automated valuation models and economic theory -- Automated Valuation Models for the Granting of Mortgage Loans in Germany74 -- An estimative model of Automated Valuation Method in Italy -- Emerging Markets Under Basel III: Can Moral Hazard lead to systematic risk and Fragility? Analysis of REIT's in Turkey -- An Application of Short Tab MCA to Podgorica -- Spatial analysis of residential real estate rental market with geoadditive models -- A Spatial Analysis for the Real Estate Market Applications -- Location Value Response Surface Model as Automated Valuation Methodology. A Case in Bari -- Further Evaluating the Impact of Kernel and Bandwidth Specifications of Geographically Weighted Regression on the Equity and Uniformity of Mass Appraisal Models -- Dealing with Spatial Modelling in Minsk -- Before and after the quake: using multi level modeling techniques as an AVM tool -- The multilevel model in the computer-generated appraisal -- Automated Valuation Methods in Real Estate Market a Two-Level Fuzzy System -- An Application of RST as Automated Valuation Methodology to Commercial Properties. A case in Bari -- The Theory and Practice of Comparable Selection in Real Estate Valuation -- Reducing the Appraisal Bias in Manual Valuations With Decision Support Systems -- An Application of Regressed Discounted Cash Flow as an Automated Valuation Method: a Case in Bari -- Automatic research of the capitalization rate for the residential automated valuation: an experimental study in Cosenza (Italy) -- Automated Procedures Based on Market Comparison Approach in Italy -- Short Tab Market Comparison Approach. An Application to the residential real estate market in Bari -- Conclusions.
Keywords: Computational intelligence; Econometrics; Financial services industry; Computational Intelligence; Quantitative Economics; Financial Services